A social media survival guide how to use the most popular platforms and protect your privacy - Karle, Melody A., 1979- (Rowman & Littlefield, 2020)
"This book helps those who want to use social media but are not necessarily Web-savvy navigate the most popular networking sites available. Privacy and technical information about how social media platforms function are explained, so everyone can make informed decisions about how to connect online"--